Pengaruh Media Sosial Tik Tok terhadap Perkembangan Belajar Siswa di SMA Kota Pekalongan - Hilda Prajayanti; Ana Setyowati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
The development in this era of globalization is skyrocketing with many of the latest technological innovations. Many social media have also sprung up with different versions and functions. Indonesia is one of the countries with the most Facebook users in the world with the number of users reaching 110 million accounts. Meanwhile, Instagram users in 2017 have reached more than 45 million people so that it makes students curious and want to try using various kinds of social media. One of the social media that is widely used by students today is tik tok social media. Tik Tok social media is audio-visual media that can be seen and heard. The use of tik tok social media is because for them this social media can entertain them when they are bored. Reduced student study time due to overuse of social media so that curiosity arises and never lags behind investigating cyberspace. The purpose of this study is to determine how much influence tik tok social media has on the learning achievement of high school students in Pekalongan City. The type of research used is analytic observational study research with cross sectional research design. Based on the results of hypothesis testing carried out, it can be concluded that there is an influence on the use of tiktok social media on the learning development of students in Pekalongan City high schools